Activation of Elemental Sulfur at a Two‐Coordinate Platinum(0) Center. Issue 36 (18th August 2016) - Roy, Sudipta; Schürmann, Christian J.; Mondal, Totan; Koley, Debasis; Herbst‐Irmer, Regine; Stalke, Dietmar; Roesky, Herbert W.
Abstract: Platinum dichalcogenides have been known to exhibit two‐dimensional layered structures. Herein, we describe the syntheses, isolation, and characterization of air‐stable crystalline cyclic alkyl(amino) carbene (cAAC)‐supported monomeric platinum disulfide three‐membered ring complex [(cAAC)2 Pt(S2 )] (2 ). The highly reactive platinum(0) [(cAAC)2 Pt] complex (1 ) with two‐coordinate platinum activates elemental sulfur to give2 . The brown crystals of bis‐carbene platinum(II)monosulfate [(cAAC)2 Pt(SO4 ) x (S2 )1− x ] (4 ) have been isolated when the reaction was performed in air. The dioxygen analogue of2 was formed upon exposing the THF solution of1 to aerial oxygen (O2 ). The binding of oxygen at the Pt 0 center was found to be reversible. Additionally, DFT study has been performed to elucidate the electronic structure and bonding scenario of2, 3, and4 . Quantum chemical calculations showed donor–acceptor‐type interaction for the Pt−S bonds in2 and Pt−O bonds in3 and4 . Abstract : Elemental sulfur/oxygen was reacted with cyclic alkyl(amino) carbene stabilized platinum(0) complexes (cAAC)2 Pt 0 to give (cAAC)2 Pt(S2 )/(cAAC)2 Pt(O2 ). These complexes were characterized by spectroscopic methods. The sulfur analogues were additionally characterized by X‐ray single‐crystal diffraction. The bonding and stability of these complexes were studied by theoretical calculations (see figure).